Assessing treatability with simulated lake drawdown: Quantifying drought‐driven turbidity in source water. Issue 4 (27th July 2022) - Hannoun, Deena; Belding, Jeffrey; Tietjen, Todd; Devaney, Robert
Abstract: The Colorado River Basin is experiencing a significant drought that began in 2000. As water supplies are projected to continue declining, water managers are concerned with the ongoing treatability of Lake Mead water, which provides 90% of the source water for the Las Vegas Valley, and is a crucial link to downstream source water. The drinking water intake currently draws high‐quality, low‐turbidity water; however, turbidity is projected to increase. This study assesses treatability by quantifying projected turbidity of source water withdrawn from a drinking water intake in Lake Mead, Nevada. The water quality modeling results provide projections for Lake Mead water turbidities in the case of extreme drawdown and provide guidance for treatment staff. The underlying process incorporated existing water quality data and identified potential problems, yielding a template for hydrodynamic and water quality modeling that utilities can take advantage of to plan for future changes in source water quality.